Design for Machining - Madl, Jan (Manufacturing Technology Journal, 2009)
Concurrent engineering plays an important role in manufacturing. Cooperation among all factors relating to the realisation of products is now necessary. Production costs represent about 40% of the selling price of products and therefore design for production and for other aspects is very important
Keywords: concurrent engineering; production; machining; design; costs